Beam Steering Control Of Microstrip Patch Antenna Using Electromagnetic Band Gap - Abdulhameed, Muhannad Kaml (2019)
The use of a high-performance antenna is very important in any wireless system design. The microstrip patch antenna has been employed commonly for numerous wireless applications because of easy analysis and fabrication. It has many advantages, namely, a low profile, low cost, and light-weight. The compact microstrip patch antennas have been achieved by high and thick dielectric substrates. However, this excites the problem of surface waves, thus antenna performance is diminished, especially when changing the main lobe direction of the radiation pattern (beam steering). Mushroom-like EBG structures have attracted increasing interest because of their desirable properties such as high impedance surface for suppressing surface waves. The main problem of the mushroom-like EBG structure is the manufacturing cost and complexity due to the number of vias connecting between the EBG and the ground plane. By loading the EBGs periodically on the substrate, a band gap can be created for frequencies around the operating frequency of the antenna (6 GHz). Such structure can stop the propagation of surface waves along the high dielectric substrate material. Therefore the integration of the mushroom-like EBG structure with a patch antenna and an array antenna of high dielectric constant substrates have been done to improve their performance. By replacing every four cells of the mushroom-like EBG by the one cell of Triple Side Slotted EBG (TSSEBG), reduction in the number of vias has been achieved. The design of TSSEBG with a microstrip patch antenna array showed an enhancement in the gain (from 10.91 to 14.68) dB, directivity (from 11.65 to 15.3) dBi, efficiency (from 84% to 87%), a reduction in side lobe (from -17.9 to -27.5) dB, and reduce the number of vias from 392 to 92. Additionally, a compact EBG based antennas were proposed by combining a rectangular antenna and ideal switches with a mushroom-like EBG structure and with TSSEBG to conduct the beam steering at the E - plane and H-plane, by using band stop and band pass properties, thereby yielding the beam steering into the band pass sector. The number of vias has been reduced from 164 to 40 in the case of combining the TSSEBG with rectangular antenna and ideal switches. The improvement in gain (10.16 dB), directivity (10.5 dBi), and efficiency (93%) have been realized at 0o main lobe direction. The efficiency is 90.5%, the gain and directivity are 9.67 dB and 10.1 dBi respectively at ±20° E-plane direction. In the H-plane radiation pattern control, the efficiency is 89 %, the gain is 9.5 dB, and directivity is 10 dBi at ±18° main lobe direction. The simulation results using CST software have illustrated the EBG characteristics of controlling the antenna and array radiation. In order to confirm the simulation results, the antennas are fabricated. The measured results agree well with the simulation data. The proposed antennas can be used in satellite and wireless applications.